Divergent roles of circulating miR-133 and miR-155 in modulating angiotensin II levels among hypertensive patients in Melanesian and non-Melanesian populations - Wijaya, Shoma A.; Pujianto, Dwi A.; Prijanti, Ani R.; Widyantoro, Bambang (Narra Sains Indonesia, 2025)
The therapeutic approach to hypertension often varies across racial and ethnic groups; however, antihypertensive treatments have not yet been tailored to account for these variations in Indonesia, a country with diverse racial and ethnic groups. In addition, microRNA-133 (miR-133) and microRNA-155 (miR-155) play critical roles in cardiac muscle homeostasis and inflammatory responses, but their specific functions in hypertension remain unclear. The aim of this study was to investigate the correlation between circulating miR-133 and miR-155 levels and angiotensin II (ANG-II) levels in hypertensive patients from Melanesian and non-Melanesian populations in Indonesia. A cross-sectional study was conducted in Jayapura, Indonesia among Melanesian and non-Melanesian hypertensive patients. The levels of ANG-II were quantified using sandwich ELISA, while the relative expression of miR-133 and miR-155 levels were measured by real-time PCR. Differences between the two groups were assessed using the Mann-Whitney test, and correlations between miR and ANG-II levels were determined using the Spearman correlation test. The relative expression levels of miR-133 and miR-155 in the Melanesian group were significantly higher than in the non-Melanesian group; 6.94-fold (3.85 vs 0.55) and 2.1-fold higher (0.19 vs 0.09), respectively. MiR-133 had a moderate negative correlation with ANG-II in both Melanesian (r=-0.538; p<0.001) and non-Melanesian (r=-0.649; p<0.001). However, miR-155 had no significant correlation with ANG-II levels in either the Melanesian group (p=0.551) or non-Melanesian group (p=0.159). This study highlights that miR-133 levels are significantly correlated with ANG-II concentrations in both Melanesian and non-Melanesian hypertensive patients, suggesting that miR-133 may play a regulatory role in the ANG-II pathway. These findings provide insights into the potential of miR-133 as a biomarker for hypertension management in diverse populations.